An Actor Approach to Mediatization: Linking Politicians’ Media Perceptions, Communication Behaviour and Appearances in the News - Ketelaars, Pauline; Van Aelst, Peter (Politics of the Low Countries, 2025)
In the light of the broader debate on the mediatization of politics, this study wants to better understand how the media perceptions and media behaviour of politicians are related to their appearances in the news. We opt for an innovative actor-centred approach to actually measure the views and actions of individual politicians. We combine surveys conducted with 142 Belgian representatives with data on politicians’ external communication behaviour and on their appearances in television news, newspapers and news websites. The results show that media behaviour is not so much related to beliefs of media importance. We do find a significant positive relationship between strategic media behaviour and media attention suggesting that politicians who put in more effort appear more often in various news media. However, this positive relationship depends on the specific form of strategic communication and the political position of the legislator. Our study adds to the mediatization literature by showing how and when politicians are successful in obtaining media attention.